Pengaruh Financial Knowledge dan Financial Attitude terhadap Perilaku Keuangan Generasi Z Di Indonesia: Pendekatan PLS-SEM - Nurul Husna; Meydina Eka Cahyani; Naufal Akmal Raihan; Ghina Risty Rihhadatulaisy; Mutiasari Nur Wulan (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Financial behavior is crucial for individual and macroeconomic stability, yet many members of Generation Z tend to adopt a consumptive lifestyle and prioritize short-term enjoyment over long-term financial security. Financial knowledge and financial attitude are important parts of shaping planned behavior, which is believed to influence financial behavior. This study aims to determine the effect of financial knowledge and financial attitude on financial behavior of Generation Z in Indonesia. This type of research is quantitative with survey approach. The study population is Generation Z, born between 1997 and 2012, residing in Indonesia. A sample of 100 respondents was selected using purposive sampling. Primary data was collected through 5-point Likert scale online questionnaire distributed via Google Form. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results showed that financial knowledge had a positive and significant effect on the financial behavior of Generation Z (t-statistic 5,731 > 1,96 and p 0,000 < 0,05), while financial attitude does not significantly affect the financial behavior of Generation Z (t-statistic 1,224 < 1,96 and p 0,221 > 0,05). These findings have implications for policymakers, educators, and financial institutions to design Generation Z financial literacy programs that are more practical or directly applicable in everyday life, such as budgeting simulations, savings planning, and simple investment guidance, so that the knowledge gained is truly internalized into responsible and sustainable financial behavior